Bridgerton: to Sir Phillip, with love - Quinn, Julia (London Piatkus (Hachette India), 2003)
The fifth novel in Julia Quinn's globally beloved and bestselling Bridgerton Family series, set in Regency times and now a series created by Shonda Rhimes for Netflix. This is Eloise's story . . ..My dear Miss Bridgerton,We have been corresponding now for quite some time, and although we have never formally met, I feel as if I know you. I am writing to invite you to visit me here at Romney Hall. It is my hope that after a suitable period of time, we might decide that we will suit, and you will consent to be my wife.Did he think she was mad? Eloise Bridgerton couldn't marry a man she had never met! But before she knew it, she was in a hired carriage in the middle of the night, on her way to meet the man she hoped might be her perfect match.Except . . . he wasn't. Her perfect husband wouldn't be so moody and ill-mannered, and while Phillip was certainly handsome, he was rough and rugged, and totally unlike the London gentlemen vying for her hand. But when he smiled . . . and when he kissed her . . . the rest of the world simply fell away. Could this imperfect man be perfect for her?Find out why readers love Julia Quinn . . .'Light, pacy and full of feisty heroines' Guardian on the Bridgerton series'Julia Quinn's Bridgerton books take all of the classic tropes we know and love . . . and gives them a thoroughly modern twist. I can't focus on anything else' Stylist'Quinn is a master of historical romance' Entertainment Weekly'A smart, funny touch' Time Magazine'Like an episode of Downton Abbey mixed with a great rom-com' iBooks Best Books of March'Powered by a surfeit of dazzling wit and graced with a cast of unforgettable characters' Booklist'A romance readers will not want to put down . . . Hooray Julia!' Romance Reviews Today'Quinn writes delightfully fast-paced, funny, sparkling and bright romance' Romantic Times'The next best thing to Georgette Heyer' Gloss'Julia Quinn is one of the best historical romance novelists of our time' Heroes and Heartbreakers'Quinn excels in writing stories full of joy and delight, where laughter trembles on the edges' Happy Ever After'Full of wit, charm and smouldering attraction . . . an unputdownable story that I think romance fans will treasure' Harlequin Junkie'Quinn is incomparable! The latest addition to her beloved Bridgerton series is funny, charming, witty and wildly romantic.
Keywords: Fiction- English; Historical Fiction